MEMUDARNYA TRADISI TER-ATER PADA ERA GLOBALISASI DI DESA WARU BARAT PAMEKASAN MADURA - Roviandri, Roviandri (Research Institute and Community Engagement of UIN MADURA, 2024)
Every human being will inevitably experience changes in their life, especially in the era globalization. The Ter-ater tradition is a custom of delivering food, such as rice and side dishes or cakes to family and neighbors. This study aims to identify the factors causing the fading of the Ter-ater tradition in the era globalization in Waru Barat Village, Pamekasan. This research is qualitative. The methods used in this study include observation, interviews, and document studies. The research location is Waru Barat Village, Pamekasan, specifically in Tobalang III Hamlet. The results of the study indicate that the community has been affected by the current of globalization, leading to the fading of the Ter-ater tradition. Changes in lifestyle towards individualism, urbanization, and economic factors are the reasons behind the decline of the Ter-ater tradition.